Circulating levels of hydrogen sulfide and substance P in patients with sepsis. Issue 4 (October 2017) - Gaddam, Ravinder Reddy; Chambers, Stephen; Murdoch, David; Shaw, Geoffrey; Bhatia, Madhav
Summary: Objective: To determine alterations of circulating levels of hydrogen sulfide and substance P in patients with sepsis compared to non-sepsis patients with similar disease severity and organ dysfunction. Methods: This study included 23 septic and 14 non-septic patients during 2015–16 study period at the Christchurch Hospital Intensive Care Unit, Christchurch, New Zealand. Blood samples were collected from the time of admission to 96 h, with collection at different time points (0 h, 12 h, 24 h, 48 h, 72 h and 96 h) and subjected to measurement of hydrogen sulfide, substance P, procalcitonin, C-reactive protein, interleukin-6 and lactate levels. Results: Patients with sepsis showed higher circulating hydrogen sulfide and substance P levels compared to patients without sepsis. Hydrogen sulfide levels were significantly higher at 12 h (1.45 vs 0.75 μM; p < 0.05) and 24 h (1.11 vs 0.72 μM; p < 0.01), whereas substance P levels were higher at 48 h (0.55 vs 0.31 ng/mL; p < 0.05). Increased hydrogen sulfide and substance P levels in septic patients were associated with increased levels of inflammatory mediators – procalcitonin, C-reactive protein and interleukin-6. Conclusions: These results provide evidence that higher circulating levels of hydrogen sulfide and substance P are associated with increased inflammatory response in patients with sepsis. Highlights: Alteration of H2 S and SP levels in septic patients largely unknown. Higher circulating H2 S and SP levels found in patients with sepsis. Higher H2 S and SP levels are associated with early inflammatory response in sepsis.